The Development of Indonesia National Curriculum and Its Changes: The Integrated Science Curriculum Development in Indonesia - Beni Setiawan; Edi Suwandi (Journal of Innovation in Educational and Cultural Research, 2022)
The national curriculum of Indonesia has changed several times, more than ten times precisely. Those alterations logically result from science learning political issues, government systems, social culture, economics, and science technology in the community. This study aims to develop integrated science in the science classroom. Qualitative research and document analysis are used in this study. The result of this qualitative research is a deeper analysis of the history of science, science textbook development, and an integrated curriculum for science learning. The history of science depicts that the curriculum change impacted how science integrates with other knowledge in the curriculum. In the last curriculum, junior high school taught integrative science, which differed from integrated science. There are two primary methods used by the Indonesian government to provide textbooks to aid in the implementation of the curriculum: the government development and a non-government publishing company developing textbooks with national standards. The last finding is the integrated curriculum for science learning. There is a relationship between the philosophy of science, integrated science, and science education. This research contributes to science, especially science education, with a term of integrated science model called Biology-Physics-Chemistry and other disciplines-Philosophy (BPCO_P)